Unravelling a Direct Role for Polysaccharide β‐Strands in the Higher Order Structure of Physical Hydrogels. (23rd March 2017) - Rüther, Anja; Forget, Aurelien; Roy, Anjan; Carballo, Carolina; Mießmer, Florian; Dukor, Rina K.; Nafie, Laurence A.; Johannessen, Christian; Shastri, V. Prasad; Lüdeke, Steffen
Abstract: The mechanical properties of agarose‐derived hydrogels depend on the scaffolding of the polysaccharide network. To identify and quantify such higher order structure, we applied Raman optical activity (ROA)—a spectroscopic technique that is highly sensitive toward carbohydrates—on native agarose and chemically modified agarose in the gel phase for the first time. By spectral global fitting, we isolated features that change as a function of backbone carboxylation (28, 40, 50, 60, 80, and 93 %) from other features that remain unchanged. We assigned these spectral features by comparison to ROA spectra calculated for different oligomer models. We found a 60:40 ratio of double‐ and single‐stranded α‐helix in the highly rigid hydrogel of native agarose, while the considerably softer hydrogels made from carboxylated agarose use a scaffold of unpaired β‐strands.